Proliferative glomerulonephritis with acute renal failure-a rare manifestation in seronegative rheumatoid arthritis (Mymensingh Medical Journal, 2009)
Mymensingh Med J. 2009 Jan;18(1):84-87. The abstract of this article is available on the PubMed website